PP.53 Domestic Violence and Termination of Pregnancy: A Systematic Review of the Literature. (26th April 2013) - Hall, M; Chappell, LC; Parnell, BL; Bewley, S
Abstract : Introduction: Domestic violence (DV) during pregnancy is common and correlated with maternal and perinatal morbidity and mortality, but less is known about the association with termination of pregnancy (TOP). The aim of this research was to synthesise current evidence on the association between DV and TOP. Methods: A systematic review was undertaken, with a structured search of four databases and reference list screening. Screening of titles and abstracts (241 papers excluding duplicates) was carried by two authors and selected papers were read in full (71). Inclusion criteria were peer-reviewed publication with defined methodology studying TOP and an aspect of DV. Formal data extraction and CASP scoring of 50 quantitative and 4 qualitative studies was undertaken by two authors. PRISMA guidelines were followed. Results: 91% of studies from 19 countries found a correlation between TOP and DV, relating to physical, emotional and sexual violence. Reported prevalence of DV varied from 7–29% (recent) and 21–39.5% (lifetime). Rates were higher amongst women who did not tell their partners about the TOP. There was a consistent correlation with DV and multiple terminations. The reasons that women in violent relationships chose to terminate was examined: two studies found women who were pressurised or forced by their partner into TOP. Descriptions of contraceptive sabotage and rape-related pregnancy were also identified. Five studies using male subjects found similar results. Conclusion: DV is common among women seeking TOP. Their healthcare and safety needs differ from the general population and should be considered by care providers.